Evaluasi Manajemen Vibrio dalam Budidaya Udang Vannamei (Litopenaeus Vannamei) - Arifin, Sunanto; Witriana, Nifa Indah (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2025)
Vibrio bacteria are recognized as major pathogens in shrimp aquaculture, causing significant threats to the health and survival of Litopenaeus vannamei in intensive farming systems. Despite various control measures, the management of Vibrio populations remains a critical challenge for sustainable aquaculture, particularly in tropical environments. This study aims to evaluate the abundance and distribution of Vibrio spp. in both culture water and shrimp body tissues, while simultaneously assessing the effectiveness of management strategies applied at PT Anugrah Tanjung Gumukmas, Jember Regency, Indonesia. Data collection employed a mixed approach, combining microbiological analysis with field observations of aquaculture practices. Water and shrimp tissue samples were taken from multiple ponds, and Vibrio colony-forming units (CFU/ml) were quantified using TCBS agar, followed by species identification to determine dominant strains. The results show that Vibrio concentrations in pond water reached the highest level in pond E22 (4.3 × 10² CFU/ml) and the lowest in other ponds (1.1 × 10¹ CFU/ml), while shrimp tissue samples from pond E14 exhibited the highest bacterial count (3 × 10⁵ CFU/ml). Furthermore, Vibrio populations in shrimp were most abundant in pond E12 (8.9 × 10⁴ CFU/ml), predominantly of Vibrio alginolyticus, exceeding the normal threshold and indicating serious risks to shrimp health. These findings underscore the necessity of continuous bacterial monitoring and adaptive pond management to prevent disease outbreaks. The study contributes to the scientific literature by providing empirical evidence of Vibrio dynamics in intensive vannamei aquaculture under tropical conditions, while also offering practical implications through recommendations for improved water quality monitoring, probiotic application, and bacterial control strategies to support sustainable shrimp farming practices.